CEST MRI for the characterisation of human brain tumours - Savvopoulos, Fotios (2020)
Chemical Exchange Saturation Transfer (CEST) is a novel MRI technique that amplifies the detection of otherwise undetectable compounds. Under certain physico-chemical and experimental conditions, CEST allows the detection of compounds containing amide, amine and hydroxyl proton groups, that are in chemical exchange with free water molecules. The main focus of this work is to gain an understanding of the underlying principles of CEST, both in-vitro and in-vivo.